The utilization of zakat for improving economic growth in Indonesia (case study at BAZNAS of Kendal regency) - Syarifah, Lailatus (Journal of Islamic Economics Management and Business (JIEMB), 2021)
Purpose – This study aimed to analyse the utilization of Zakat at BAZNAS Kendal Regency.Method – This study used a qualitative approach with interview as the data collection strategy.  Result – The utilization of productive Zakat by BAZNAS of Kendal regency was implemented well.Implication – This study can assist the government in making a policy and regulation related to zakat managementOriginality – This was the first study examining zakat management in Kendal Regency.